EKSISTENSI KETUA ADAT DAYAK DESA PADA KOMUNITAS RUMAH BETANG - Annisa Dwi Lestari; Dhea Frastika; Mita; Diaz Restu Darmawan (Universitas Pendidikan Ganesha, 2023)
The Dayak Desa community in Betang House Ensaid Panjang Village, until now still maintains the existence of customs in the midst of their lives. This paper aims to reveal the existence of Ketua Adat in the midst of the current modernization period. The method used in this paper uses a qualitative method with data collection techniques by direct observation. The narratives in this paper are based on the results of in-depth interviews with informants formed in the data and information documentation. The focus of researchers in conducting mini research is on the existence of traditional leaders as seen from the seven elements of culture. The results showed that the Dayak Desa community living in Betang's house in Ensaid Panjang Village still maintained the function and existence of informal leaders. The election of the Ketua Adat Dayak Desa is based on community beliefs based on the charisma, authority and authority of the chosen figure. In addition to the figure of the traditional leader who is obeyed, the Dayak Desa community in Betang House in Ensaid Panjang Village really appreciates the house they use as a reference and guideline for customs in all their lives.